2015
DOI: 10.1371/journal.pone.0132926
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 Inhibitor (ABT-737): A Restorer of Prednisolone Sensitivity in Early T-Cell Precursor-Acute Lymphoblastic Leukemia with High MEF2C Expression?

Abstract: Early T-cell precursor-acute lymphoblastic leukemia (ETP-ALL) has been identified as a high-risk subtype of pediatric T-cell acute lymphoblastic leukemia (T-ALL). Conventional chemotherapy is not fully effective for this subtype of leukemia; therefore, potential therapeutic targets need to be explored. Analysis of the gene expression patterns of the transcription factors in pediatric T-ALL revealed that MEF2C and FLT3 were expressed at higher levels in ETP-ALL than typical T-ALL. Using human T-ALL and BaF3 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In leukemic patients, the ectopic expression of MEF2s caused by chromosomal rearrangements is responsible for the development of leukemia. A high level expression of MEF2C is observed in T-cell acute lymphoblastic leukemia (T-ALL) [ 42 , 43 ]. The chromosomal translocation generates reciprocal DAZAP1/MEF2D and MEF2D/DAZAP1 fusion genes that promotes oncogenic properties in NIH 3T3 cells [ 44 ].…”
Section: Mef2 Physiological Function and Signal Pathwaysmentioning
confidence: 99%
“…In leukemic patients, the ectopic expression of MEF2s caused by chromosomal rearrangements is responsible for the development of leukemia. A high level expression of MEF2C is observed in T-cell acute lymphoblastic leukemia (T-ALL) [ 42 , 43 ]. The chromosomal translocation generates reciprocal DAZAP1/MEF2D and MEF2D/DAZAP1 fusion genes that promotes oncogenic properties in NIH 3T3 cells [ 44 ].…”
Section: Mef2 Physiological Function and Signal Pathwaysmentioning
confidence: 99%
“…Although there were too few patients in the present series to draw any definitive conclusions, I-5q marks a particularly high-risk subgroup of immature/ETP ALL for which alternative targeted therapies should be developed. Among them, JAK/STAT inhibitors, which are highly effective in ETP-ALL xenograft models, 43 and the BCL2 inhibitor ABT-737, which restores the sensitivity to steroids in cell lines with high MEF2C expression, 44,45 might be considered in the treatment of these refractory leukemias.…”
Section: Genetic Profile Links Interstitial 5q With Immature/early T-mentioning
confidence: 99%
“…Lu et al [13] tested the role of DNA methyltransferase inhibitor decitabine in pretreating ETP-ALL through the vitro test and suggesting that decitabine could enhance the chemosensitivity in ETP-ALL. [14] Sachiko Kawashima-Goto [15] suggested the Bcl2 inhibitor (ABT-737) can recover the sensitivity to prednisolone in leukemic cells with a high expression of MEF2C. Based on this, inhibition of Bcl2 might become a therapeutic candidate for ETP-ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed the combination of CDKN1B deletions with the expression of MEF2C considered as a driving oncogene in ETP-ALL. And Kawashima-Goto et al [15] suggested BCL2 inhibitor (ABT-737) may be a restorer of prednisolone sensitivity in ETP-ALL with high MEF2C expression. Lmo2 is an oncogenic transcription factor that is frequently over-expressed in T-ALL including ETP-ALL which must combine with its partner SCL or LYL1 to drive leukemia.…”
Section: Discussionmentioning
confidence: 99%